Postoperative Disability After Long Corrective Fusion to the Pelvis in Elderly Patients With Spinal Deformity. Issue 14 (15th July 2018) - Togawa, Daisuke; Hasegawa, Tomohiko; Yamato, Yu; Yoshida, Go; Kobayashi, Sho; Yasuda, Tatsuya; Oe, Shin; Banno, Tomohiro; Arima, Hideyuki; Mihara, Yuki; Ushirozako, Hiroki; Matsuyama, Yukihiro
Abstract : Study Design: A prospective case series analysis. Objective: The purpose of this study was to investigate the degree of difficulty in daily activities of adult spinal deformity (ASD) patients after corrective long fusion to the pelvis, with an emphasis on bend forward activities. Summary of Background Data: No prospective studies have been reported regarding the postoperative impairments and their time course after long fusion in ASD patients. Methods: One-hundred three patients [26 men, 77 women; mean age 68 (50–82) years] who underwent corrective long fusion from the thoracic spine to the pelvis were included. As a control group, 578 volunteers [213 men, 365 women; mean age 72 (50–84)] who underwent musculoskeletal examination were included. Seven daily activities were assessed using Disability Scores (DS10), which ask patients to rate the difficulty of actions from 1 (very easy) to 10 (very difficult). The activities selected were a) gait, b) ability to trim toe nails, c) lie supine, d) perform personal hygiene, e) put on pants, f) pick up an item from the floor, and g) get down on all fours. Each of these activities were rated by all volunteers and patients at five assessment points in 2 years. Questionnaires (ODI, SRS-22, and DS10) were administered preoperatively, at discharge, 6 months, 1 year, and 2 years postoperatively. Radiographic parameters and clinical results of the control group were compared with those of the ASD patients and the patients with different upper instrumented vertebrae. Results: Although successful clinical results and deformity corrections were achieved, the ASD patients reported significant difficulty in b), d), e), f), and g) after the surgery (all P < 0.0001), regardless of the fusion length. The difficulty gradually improved toward 2 years but did not reach preoperative status. Conclusion: Activities requiring patients to bend forward were more difficult for elderly ASD patients postoperatively. Level of Evidence: 3